PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KATALOG UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 5 SURAKARTA - Widalismana, Merlyn; Baedhowi, Baedhowi; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2016)
The purpose of this research is 1) to develop media based learning catalog valid for improving student learning outcomes and 2) to know the effectiveness of media based learning catalog quick to improving student learning outcomes on economic subject in the SMA N 5 Surakarta. This research is research method and development (R&D). Data collection techniques are used observation, interview, questionnaires, test and document. The result of development of research based instructional media catalog create more effective learning, and motivate students create creative ideas in learning can improving student learning outcomes. Catalogue-based learning media posttest results of the economic value of the learning outcomes of students of class XII S2 and XII S3 between class control and class experiments showed that the average posttest control group is 79,22 while the average posttest experiment class is 82,66. Once in the t-test analysis using IBM SPSS 21 software obtained significance value of 0,019 > a (0,05), which showed that H1 results of experimental class better than the control class with significant differences. Based on the results of the learning outcomes of economic value posttest control class and experimental class also analyzed by t-test formula. Price t obtained from posttest control class and experiment class is 2,404 with a price t table is 1,999. Thus t price > t table, means an increasing in economic class student learning outcomes experiment better than the control class. This shows that media-based learning catalog results further enhance the development of the economic value of student learning outcomes compared with no use of instructional media as before. The conclusion of this research is based instructional media valid catalog for increasing learning results and based instructional media effective catalog for increasing the results learning. Keywords: Development, Catalog, Media, Outcomes Learning